Evidence that N-acetylaspartylglutamate is the Astrocyte-Targeted Neurovascular Coupling Agent that Regulates Slow Tonic Control of Brain Blood Flow - Morris, H Baslow; David, N Guilfoyle (Journal of Glycomics And Metabolism, 2016)
N-acetylaspartylglutamate (NAAG) is the highest concentration dipeptide present in brain. It is found primarily in neurons but its function is unclear. NAAG is synthesized by neurons from N-acetylaspartate and glutamate (Glu), maintained at mM concentrations and is released non-synaptically to extracellular fluid (ECF). NAAG is a non-excitatory form of Glu, and is targeted to the metabotropic group II Glu receptor 3 (mGluR3) on the surface of astrocytes. After docking with the receptor, Glu is released by the action of NAAG peptidase. Previously, it was shown for the first time that an NAAG-peptidase inhibitor reduced global cerebral blood flow (CBF) in mouse brain but did not affect their physical performance. Recently, it has been demonstrated that there are two separate systems involved in neurovascular coupling by astrocytes, one is a rapid focal phasic response providing energy for stimulation-induced neuronal activity, and the other a slower global tonic response providing energy for ongoing metabolic activities. Many neurovascular coupling mechanisms are known that regulate phasic changes in CBF, but how the brain accomplishes tonic control is unknown. In this paper we bring together two separate lines of inquiry, the decades’ long search for the function of NAAG, and the more recent search for the mechanism of tonic neurovascular control. Herein, we present evidence that NAAG is the neurovascular coupling agent that regulates tonic changes in CBF via the astrocyte mGluR3-NAAG peptidase connection.
Keywords: brain energy metabolism; cerebral blood flow; glucose; glutamate; N-acetylaspartate; N-acetylaspartylglutamate; neurovascular coupling